An Update on Formic Acid Dehydrogenation by Homogeneous Catalysis - Guan, Chao; Pan, Yupeng; Zhang, Tonghuan; Ajitha, Manjaly J.; Huang, Kuo‐Wei (Chemistry, an Asian journal, 2020)
Formic acid (FA) has been extensively studied as one of the most promising hydrogen energy carriers today. The catalytic decarboxylation of FA ideally leads to the formation of CO2 and H2 that can be applied in fuel cells. A large number of transition‐metal based homogeneous catalysts with high activity and selectivity have been reported for the selective FA dehydrogentaion. In this review, we discussed the recent development of C,N/N,N‐ligand and pincer ligand‐based homogeneous catalysts for the FA dehydrogenation reaction. Some representative catalysts are further evaluated by the CON/COF assessment (catalyst on‐cost number)/(catalyst on‐cost frequency). Conclusive remarks are provided with future challenges and opportunities. Fueling the future: Formic acid (FA) has been extensively studied as one of the most promising hydrogen energy carriers today. In this review, we discussed the recent development of C,N/N,N‐ligand and pincer ligand‐based homogeneous catalysts for the FA dehydrogenation reaction. The CON/COF assessment (catalyst on‐cost number)/(catalyst on‐cost frequency) was highlighted with conclusive remarks on the future challenges and opportunities.